The method for optimizing the iron content in the structural material Zr1%Nb for fuel element cladding of NPP nuclear reactors - Yefimov, O.V.; Pylypenko, M.M.; Lyubchyk, L.M.; Potanina, T.V.; Kravchenko, V.P.; Yesypenko, T.O.; Harkusha, T.A. (Problems of Atomic Science and Technology, 2023)
The mathematical method of optimizing the amount of the alloying element Fe in structural zirconium alloys Zr1%Nb of fuel elements cladding of nuclear reactor-cores of nuclear power plants on the basis of physical experiments to increase their corrosion resistance is considered. Alloying the Zr1%Nb alloy with Fe is promising in the development of the technology for the production of domestic materials for fuel elements claddings for reactors with high reliability and safety. To process the results of experimental studies of corrosion of zirconium alloy with different Fe content, a mathematical method of two-dimensional polynomial comb regression was proposed with its implementation in the Python programming language based on the theory of “machine learning”. The application of this method made it possible to determine the optimal amount of the alloying element Fe for zirconium alloy Zr1%Nb of fuel elements cladding of nuclear power plant reactors with pressurized water.